BERMAIN DAN PERMAINAN ANAK USIA DINI - Siti Nur Hayati; Khamim Zarkasih Putro (UIR PRESS, 2021)
This study aims to find out that playing and games have very important benefits for growth and development in early childhood. This paper uses the literature study method which is carried out by reviewing and/or exploring several books, journals, as well as notes and other information or data that are judged to be following the study or research. In this study, it is stated that playing and games can make a positive contribution to the development of early childhood, namely, it can develop all aspects of development which include aspects of religious morals, social-emotional, language, cognitive, physical motor, and also art. In addition, there are also goals, characteristics, functions, benefits, and stages of development of early childhood play and are also equipped with playing conditions and games as well as examples of games that can stimulate developmental aspects in children. Playing and playing games can help children improve their aspects in an integrated and comprehensive manner. A safe and comfortable play environment is needed for children to explore and get stimulation for growth and development.